Search for direct production of electroweakinos in final states with one lepton, missing transverse momentum and a Higgs boson decaying into two b-jets in pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; Kolb, Mathis; Krishnan, Anjali; et al. (The European physical journal. C, Particles and fields, 2020)
The results of a search for electroweakino pair production pp→χ~1±χ~20 in which the chargino chi 1$$χ~1±) decays into a W boson and the lightest neutralino chi 1$$χ~10), while the heavier neutralino chi 2$$χ~20) decays into the Standard Model 125 GeV Higgs boson and a second chi 1$$χ~10 are presented. The signal selection requires a pair of b-tagged jets consistent with those from a Higgs boson decay, and either an electron or a muon from the W boson decay, together with missing transverse momentum from the corresponding neutrino and the stable neutralinos. The analysis is based on data corresponding to 139 fb-1 of √s=13 TeV pp collisions provided by the Large Hadron Collider and recorded by the ATLAS detector. No statistically significant evidence of an excess of events above the Standard Model expectation is found. Limits are set on the direct production of the electroweakinos in simplified models, assuming pure wino cross-sections.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration: G. Aad, C. Anders, G.V. Andrei, A. Bolz, M. Dunford, D.E. Ferreira de Lima, S. Franchino, L. Helary, J. Jongmanns, M. Klassen, M. Kolb, A. Krishnan, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, P. Ott, M. Sahinsoy, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S. Weber, M. Wessels, X. Yue [und viele weitere]
Gesehen am 27.10.2020